The Effect of the Motor Vehicle Tax Amolishment and Payment Ease Program on Taxpayer Compliance (West Surabaya Samsat) - Avariano Yusuf Ardiansyah; Eko Budi Santoso (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine the effect of the Tax Amnesty Program and Ease of Payment of Motor Vehicle Tax (PKB) on Taxpayer Compliance at the West Surabaya SAMSAT Office. The data used in this study are primary data obtained from a survey of 100 taxpayers using the purposive sampling method. The data were analyzed using descriptive statistics, validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results of the study indicate that the Tax Amnesty Program does not have a significant effect on Taxpayer Compliance. This is because this program does not provide a long-term solution for taxpayers who are in arrears and does not address the underlying reasons for tax arrears. In addition, weak law enforcement against tax arrears makes Taxpayers feel that the risk of tax evasion is lower than the benefits obtained from participating in the program. On the other hand, the Ease of Payment of PKB has a positive and significant effect on Taxpayer Compliance. Various services provided by SAMSAT, such as online payments, drive-thru, and payments through minimarkets, make it easier for taxpayers to pay their taxes, which ultimately increases taxpayers' willingness to comply with tax regulations.